2013
DOI: 10.1111/joic.12029
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Correlation and Clinical Outcome of Intra‐Procedural Stent Thrombosis in Patients Undergoing Primary Percutaneous Coronary Intervention for Acute Coronary Syndrome

Abstract: IPST was a rare complication of PCI in the setting of ACS. It correlated with lesion morphology, presence of thrombus at baseline and was more likely to cause MACEs in 30 days and 1-year follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Xu et al performed a retrospective study of 1,901 patients with acute coronary syndrome who underwent primary PCI. 81 Patients with IPST demonstrated involvement of significantly more bifurcation lesions and had more thrombus burden at baseline. The IPST group also had more major adverse cardiac events at their 30-day and one-year follow-ups.…”
Section: Stent Thrombosis: the Literature At A Glancementioning
confidence: 93%
“…Xu et al performed a retrospective study of 1,901 patients with acute coronary syndrome who underwent primary PCI. 81 Patients with IPST demonstrated involvement of significantly more bifurcation lesions and had more thrombus burden at baseline. The IPST group also had more major adverse cardiac events at their 30-day and one-year follow-ups.…”
Section: Stent Thrombosis: the Literature At A Glancementioning
confidence: 93%
“…IPST is a risk factor for major adverse cardiovascular events. 1 The reported frequency of IPST ranges from 0.5 to 1.2%.…”
Section: Images In Cardiovascular Medicine Intraprocedural Stent Thromentioning
confidence: 99%
“…3 It has also been demonstrated that in patients with coronary artery disease (CAD), lower STB might represent a predictor of major adverse cardiovascular events after PCI. 4 Frontal QRS-T angle (QRSTa), one of the electrocardiographic parameters to identify high-risk patients, reflects the myocardial depolarization and repolarization heterogeneity, particularly in patients with CAD. 5 An abnormal frontal QRSTa has been suggested to be closely linked to increased cardiovascular mortality, 6 and it has been found to predict poor prognosis in patients with ACS.…”
Section: Introductionmentioning
confidence: 99%